Preparation of PVDF UF Membranes under an External Electric Field with PVP as Additive - Shi, Baoli; He, Jing (Journal of Membrane and Separation Technology, 2014)
In this study, PVDF UF membranes were prepared with PVP as additive via a favorable method of applying high voltage external electric field (2kV) through the immersion precipitation phase inversion process. The influence of external electric field on the structure, surface functional groups, membrane potential, and surface hydrophilicity of the membranes were researched. In addition, anti-fouling property and separation performance of the membranes were also investigated. The results indicated that the protein adsorption amount on the electric treated membranes was distinctly reduced. Especially for the electric treated PVDF membrane with PVP K70 as additive, the value of water contact angle reached 75.4° and the protein adsorption amount decreased 76 %, reaching 20.39 µg·cm-2. The separation performance of the electric treated membrane was also superior to that of the un-treated membrane. All the experimental results indicated that this electric treated approach open a promising way for the modification of PVDF membrane because it combined membrane preparation and modification in only one physical step without additional chemical reagents.